Indonesia's Position and Participation in The Global Value Chain of The Agriculture Sector - Herry Nugraha; Rita Nurmalina; Noer Azam Achsani; Arif Imam Suroso; Suprehatin Suprehatin (Jurnal Manajemen dan Agribisnis, 2025)
Background: The agricultural sector in Indonesia, contributing 13.7% to GDP and employing 30% of the workforce, is critical to the nation's economy. Despite its importance, the country's participation in the agricultural global value chain (GVC) faces persistent challenges, particularly in advancing agro-processing and integrating into high-value production. Purpose: This study analyzes Indonesia's GVC position and participation from 2007 to 2021, using the UIBE GVC Index and ADB ICIO data.Design/Methodology/Approach: Descriptive statistics and linear regression methods are used to assess Indonesia's forward and backward GVC participation compared to that of 62 other countries worldwide.Findings/Result: Findings reveal significant declines in Indonesia's backward participation, reflecting progress toward self-sufficiency, yet limited participation in complex forward and backward linkages underscores deficiencies in technological infrastructure and value-added exports. Moderate engagement in simple forward linkages highlights the need for targeted investments to boost competitiveness. Strategic interventions in infrastructure, advanced inputs, capacity-building, and global collaborations are essential for strengthening Indonesia's agricultural GVC role. Conclusion: To enhance GVC participation, Indonesia must address technological, infrastructure, and policy gaps. Strategic investments in agro-processing, advanced inputs, supply chain modernization, and international partnerships are critical to boosting competitiveness and export performance. Originality/Value (State of the Art): This study provides comprehensive insights for policymakers and stakeholders, emphasizing innovative strategies to enhance Indonesia’s global agricultural presence and achieve sustainable growth. Keywords: Agriculture, GVC Position, GVC Participation, Global Value Chain (GVC), UIBE GVC Index.